PENGARUH KOMPENSASI, KETERLIBATAN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DIVERSEY BALI - Ni Luh Gede Putu Purnawati; Ida Ayu Nyoman Yuliastuti; Pande Ketut Ribek (Jurnal Ilmiah Satyagraha, 2023)
Performance is an important thing in order to support the smoothrunning of the organization in achieving its goals and can be created if there is a high spirit of the employees. From the observation of thephenomenon of decreasing employee performance at PT. Diversey Bali iscaused by several factors including compensation, work involvement andworkload. This study aims to determine the effect of compensation, workinvolvement and workload on employee performance at PT. Diversey Bali.The sampling technique used is a saturated sample using all employees ofPT. Diversey Bali, totaling 33 people. The method of analysis used multiplelinear regression using the SPSS IBM Statistics 24.0 Portable program.From the results of the analysis obtained the results of the effect ofcompensation, work engagement and workload on employee performanceat PT. Diversey Bali is positive and significant. From the results ofmultiple linear regression analysis, the regression equation Y= 14,663 +0.374 X1 + 0.444 X2 1.135 X3¬can be explained that the pattern ofinfluence of compensation variables (X1) and work involvement (X2) onthe dependent variable of employee performance (Y) is positive, meaningthat if the variable If self-efficacy and organizational climate increase,employee performance will increase or vice versa. While the effect of theworkload variable (X3) on employee performance (Y) is negative, meaningthat if the workload variable increases, employee performance willdecrease and vice versa. From the results of the tdi test, it can be seen thatself-efficacy and organizational climate partially have a positive andsignificant effect on employee performance. This means that the higher thecompensation or work involvement, the higher the resulting performance.Meanwhile, workload has a negative and significant effect on employeeperformance. This means that the higher the workload, the lower theresulting performance.